Politische Einstellungen in privilegierten und benachteiligten Großstadtquartieren in Deutschland - Läzer, Katrin Luise (Q-Serie, 2008)
In the course of structural change from an industrial society to a service society large cities in Germany and Europe undergo a profound economic, social and political process of change, which leads to a sharper segregation in the cities. The social spatial concentration of unemployment, poverty and social exclusion in underprivileged city areas removes such areas in their social standards and life chances far from the urban life of the majority. This raises the question of urban social and political integration. The doctoral thesis is dedicated to one aspect of the question regarding integration of cities. It focuses on the political perceptions and attitudes of their citizens. A noticeable declining of turnouts of voters and an increasing "disenchantment with politics", which signal the disappointment and resignation of disadvantaged groups toward policy, and a tendency towards desolidarization in privileged areas give reason to analyze political attitudes in cities. Therefore, the doctoral thesis deals with local political attitudes in privileged and underprivileged city areas in four cities: Berlin, Cologne, Leipzig and Mannheim. Political attitudes are operationalized as political trust, the perception of responsivity of local policy, political participation as well as solidarity, social confidence and social commitment. A telephone poll was carried out with 400 standardized interviews in each of four privileged and four underprivileged quarters. In total, 3200 interviews were conducted and included in the statistical analysis.